Determinants of Performance of Village Government in Early Implementation of Village Law - Slamet Rosyadi; Bambang Tri Harsanto; Khairu Roojiqien Sobandi (Universitas Sultan Ageng Tirtayasa, 2020)
Decentralization policy in Indonesia has been expanded to the level of the village since 2015. The main purpose of this policy is to improve the performance of village government in providing more effective public service and efforts to poverty alleviation in rural areas. The authors argue that social capital, governance practices, leadership capacity, and resources can be important factors influencing the performance of village government. However, knowledge about to which extent village governments present their actual performance concerning social capital, governance practices, leadership and resources is still not sufficient yet. Using survey data conducted in 2015, this study aims to describe the early state of village government performance and examines links among social capital, governance practices, leadership capacity and resources with village government performance. The survey has selected 10 villages representing upland and lowland areas in Banyumas Regency, Central Java Indonesia. From each village, we choose 30 community leaders to express their opinion on our variables. Data is analyzed by descriptive statistics and ordinal regression since it was an ordinal scale. The result shows that village governments still have a good ability to formulate strategic planning, to realize development outcomes relevant to community needs, to utilize public participation in decision-making stages, to develop community organization capacity and to empower villagers.